A importância das Unidades de Conservação no Brasil - Márcio Luís Hassler (Sociedade & Natureza)
The exhaustion of several natural resources in the group, nowadays, the questionamentos on whathas been made to avoid a damage every time larger to the nature. Damage this that will be reflectedin the own society that depends on the natural ways to survive. The Units of Conservation start toexercise a fundamental paper in the process of environmental protection as they passed, along itsimplantation process, to be assumed officially by the State, managing the conservationist spacesstarting from the interest and of the power publics.